125I-Sodium Iothalamate in the Determination of the Glomerular Filtration Rate - Malamos, B.; Dontas, A. S.; Koutras, D. A.; Marketos, S.; Sfontouris, J.; Papanicolaou, N. (Nuklearmedizin - NuclearMedicine, 1967)
One hundred 125I-sodium iothalamate and endogenous creatinine clearances in 36 subjects were compared with standard inulin clearance measurements. There was a very close correlation of the urine/plasma ratios between any two of the three clearances studied, hence both labelled iothalamate and creatinine can be relied upon for the estimation of the glomerular filtration rate in clinical practice. The mean ratio of 125I-sodium iothalamate to inulin clearance was 1.01 and that of creatinine to inulin 1.03. It is concluded that the clearance of 125I-sodium iothalamate can be substituted for the clearance of inulin in clinical determinations of the glomerular filtration rate but that in centres without radioisotope facilities the endogenous creatinine clearance can be used instead.